2021
DOI: 10.1155/2021/1457089
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Superoxide by BAP31 through Its Effect on p22phox and Keap1/Nrf2/HO‐1 Signaling Pathway in Microglia

Abstract: Reactive oxygen species (ROS) production by activation of microglia is considered to be a major cause of neuronal dysfunction, which can lead to damage and death through direct oxidative damage to neuronal macromolecules or derangement of neuronal redox signaling circuits. BAP31, an integral ER membrane protein, has been defined as a regulatory molecule in the CNS. Our latest studies have found that BAP31 deficiency leads to activation of microglia. In this study, we discovered that BAP31 deficiency upregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Increased lipid peroxidation and enhanced ROS are characteristics of ferroptosis, making it different from other forms of cell death such as apoptosis, necrosis, and autophagy [ 26 ]. It has been reported that BAP31 – an integral ER membrane protein – is involved in ROS production through p22 phox and Keap1/Nrf2/HO-1 signaling pathway in microglia [ 27 ]. However, whether BAP31 plays a role in ferroptosis remains uncertain.…”
Section: Resultsmentioning
confidence: 99%
“…Increased lipid peroxidation and enhanced ROS are characteristics of ferroptosis, making it different from other forms of cell death such as apoptosis, necrosis, and autophagy [ 26 ]. It has been reported that BAP31 – an integral ER membrane protein – is involved in ROS production through p22 phox and Keap1/Nrf2/HO-1 signaling pathway in microglia [ 27 ]. However, whether BAP31 plays a role in ferroptosis remains uncertain.…”
Section: Resultsmentioning
confidence: 99%